Dynamic Characteristics of Blade with Viscoelastic Damping Block Based on Complex Eigenvalue Method - Jiao Wang; Yue-hao Zhang; Tao Yu; Qing-kai Han (Shock and Vibration)
A novel method for vibration suppression is proposed, adding a viscoelastic damping block to the root of the blade. The dynamical equation for a rotational viscoelastic damping block-blade (VE-blade) in a centrifugal force field and aerodynamic force field is established to calculate the dynamical natural frequency and responses of the VE-blade. Complex modulus model is applied to represent the constitutive law of viscoelastic material and shear force acting on the VE-blade formulates the effect of viscoelastic damping at the root interfaces. The dynamical equation of the system is established and the Galerkin method is used to discretize the partial differential equations to a 3-DOF system so as to compute the dynamic natural frequencies and responses of the VE-blade. Then the differential equations of motion with 3-DOF are numerically solved by using complex eigenvalue method. A cantilever VE-blade is simplified according to testing the first three natural frequencies of the real blade to obtain geometric parameters of cantilever beam. The effects of various parameters including thickness, storage modulus, loss factor of viscoelastic damping block, and rotating speed on natural frequency and modal damping ratio of VE-blade are discussed in detail.